RACIAL DISCRIMINATION SUFFERED BY BLACK PEOPLE REFLECTED IN HIDDEN FIGURES FILM - Hatta, Jilan Tsamarah (Journal of English Literature and Linguistic Studies, 2025)
This research discusses racial discrimination that occurs in the film Hidden Figures. The film tells the story of three black women who experienced racial discrimination in their lives. The purpose of this research is to classify the kinds of racial discrimination that often appear in the film using the theory of Pincus (1996) to find the kinds of racial discrimination suffered by the main characters. This study also found the impact of racial discrimination from three aspects, namely psychological, social, and economic. In this research, we used a qualitative descriptive method. The results of this study found that institutional discrimination is the most common kind of racial discrimination in the film. The psychological impact suffered by the main characters is stress, unhappiness, and dissatisfaction with their lives. The social impact is that black people often get violent. And finally, the economic impact is the low job position and low salary of black people in the Hidden Figures film.